GAMBARAN EMOSI DAN TINGKAT KECEMASAN PADA PASIEN HIPERTENSI DI PUSKESMAS BAHU - Kati, Richard K.; Opod, Hendri; Pali, Cicilia (eBiomedik, 2018)
Abstract: Anxiety and poor emotional management may trigger the occurence of hypertension. In reverse, hypertension is able to cause uncontrolled anxiety and emotion. This study was aimed to determine the emotional and anxiety level of patients with hypertension at Puskesmas Bahu (Primary Heath Center). This was a descriptive study with a cross-sectional design. Hamilton Anxiety Rating Scale was used to measure the anxiety level, and Positive Affect-Negative Affect Schedule was used to determine the emotion overview of hypertensive patients. Subjects of this study were all hypertensive patients who came to Pukesmas Bahu during the period of October to November 2017. There were 78 patients as respondents involved in this study; 49 (62.8%) females and 29 (37.2%) males. The results showed that 4 (5.1%) respondents had dominant negative affect, while the other 74 (94.9%) respondents had dominant positive affect. Dealing with the anxiety level, there were 23 (29.5%) respondents with mild anxiety level, 21 (26.9%) respondents with severe anxiety level, 20 (25.6%) respondents with moderate anxiety level, 10 (12.8%) respondents had no anxiety, and the other 4 (5.1%) respondents had very severe anxiety. Conclusion: Most hypertensive patients at Puskesmas Bahu had dominant positive affect frequently associated with mild anxiety.Keywords: emotion, anxiety, affect, hypertensionAbstrak: Kecemasan dan manajemen emosi yang buruk dapat mencetuskan terjadinya hipertensi. Hipertensi juga dapat menyebabkan kecemasan dan emosi menjadi tidak terkendali. Penelitian ini bertujuan untuk mengetahui gambaran emosi dan tingkat kecemasan pada pasien hipertensi di Puskesmas Bahu. Jenis penelitian ialah deskriptif dengan desain potong lintang. Hamilton Anxiety Rating Scale digunakan untuk mengukur tingkat kecemasan dan Positive Affect Negative Affect Schedule digunakan untuk mengetahui gambaran emosi pasien hipertensi. Subyek penelitian ialah seluruh pasien hipertensi yang datang berkunjung ke Puskesmas Bahu pada periode Oktober sampai November 2017. Terdapat 78 responden dalam penelitian ini terdiri dari 49 orang (62,8%) perempuan dan 29 orang (37,2%) laki-laki. Gambaran emosi yang didapatkan ialah sebanyak 4 responden (5,1%) memiliki afek negatif yang dominan sedangkan 74 responden (94,9%) memiliki afek positif yang dominan. Gambaran tingkat kecemasan yang didapatkan ialah kecemasan ringan sebanyak 23 orang (29,5%), kecemasan berat 21 orang (26,9%), kecemasan sedang 20 orang (25,6%), tidak ada kecemasan sebanyak 10 orang (12,8%), dan kecemasan berat sekali sebanyak 4 orang (5,1%). Simpulan: Sebagian besar pasien dengan hipertensi di Puskesmas Bahu memiliki afek positif yang dominan dan tersering disertai kecemasan ringan.Kata kunci: emosi, kecemasan, afek, hipertensi